Woman, Freemason and Spanish: Freemasonry and the Origins of Feminism (Global Journal of Human-Social Science, 2014)
This paper studies the role of women in the Spanish Masonry, especially during the nineteenth century. The role assigned to women in the Constitutions of Anderson (1723) mentioned, the origins of Freemasonry are cited Adoption, then, the role assigned to women in Freemasonry is analyzed, mainly by analyzing the case of Spain, where integrated in Masonry women were also, in many cases, that laid the foundation of the Spanish Feminism.
Keywords: freemasonry; history of women; feminism spanish; xix century